2005
DOI: 10.1186/1471-2156-6-53
|View full text |Cite
|
Sign up to set email alerts
|

RB1 gene mutation up-date, a meta-analysis based on 932 reported mutations available in a searchable database

Abstract: BackgroundRetinoblastoma, a prototype of hereditary cancer, is the most common intraocular tumour in children and potential cause of blindness from therapeutic eye ablation, second tumours in germ line carrier's survivors, and even death when left untreated. The molecular scanning of RB1 in search of germ line mutations lead to the publication of more than 900 mutations whose knowledge is important for genetic counselling and the characterization of phenotypic-genotypic relationships.ResultsA searchable databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 39 publications
3
57
1
4
Order By: Relevance
“…Exon 20 contains several hotspots for recurrent mutations of high functional impact 37 . The other loci, including one located in exon 23 of Rb1 , had significantly lower mean γH2AX ratios, ranging from 0.72 to 1.01 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exon 20 contains several hotspots for recurrent mutations of high functional impact 37 . The other loci, including one located in exon 23 of Rb1 , had significantly lower mean γH2AX ratios, ranging from 0.72 to 1.01 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One exception is in retinoblastoma where it has been found that low-penetrance RB1 mutations tend either to lead to a reduction in the amount of Rb protein produced (through promoter or splice site mutations) or yield a partially functional Rb molecule through missense mutation or in-frame deletion (Onadim et al 1992; Kratzke et al 1994; Bremner et al 1997; Otterson et al 1997; Scheffer et al 2000; Genuardi et al 2001; Harbour 2001; Klutz et al 2002; Lefévre et al 2002; Valverde et al 2005; Sánchez-Sánchez et al 2005; Sampieri et al 2006; Gámez-Pozo et al 2007; Park et al 2008; Hung et al 2011). Of particular interest is the category of temperature-sensitive mutations in the Rb pocket domain (ΔAsn480, Arg661Trp, Cys712Arg) whose ‘reversible fluctuations’ in a threshold level of Rb pocket-binding activity could be responsible for their characteristic low penetrance (Otterson et al 1999).…”
Section: Influence Of Mutation Type On Penetrancementioning
confidence: 99%
“…These exons were analyzed since they have the highest frequencies of nonsense mutations in retinoblastoma patients ([18] and http://rb1-lovd.d-lohmann.de/). In line with our findings using RT-PCR screening, we observed no mutations in these “hot spot” exons when analyzing the same samples using genomic DNA, indicating that the likelihood of any mutation escaping our cDNA sequencing analyses are negligible.…”
Section: Resultsmentioning
confidence: 99%